Advances in Neural Computation, Machine Learning, and Cognitive Research II Selected Papers from the XX International Conference on Neuroinformatics, October 8-12, 2018, Moscow, Russia - Kryzhanovsky, Boris; Dunin-Barkowski, Witali; Redko, Vladimir; Tiumentsev, Yury (Studies in Computational Intelligence,, 2019)
This book describes new theories and applications of artificial neural networks, with a special focus on addressing problems in neuroscience, biology and biophysics and cognitive research. It covers a wide range of methods and technologies, including deep neural networks, large-scale neural models, brain-computer interface, signal processing methods, as well as models of perception, studies on emotion recognition, self-organization and many more. The book includes both selected and invited papers presented at the XX International Conference on Neuroinformatics, held in Moscow, Russia on October 8-12, 2018.